Current knowledge of the immune reconstitution inflammatory syndrome in Whipple disease: a review - Song, Xiangyi; Duan, Ruifeng; Duan, Liwei; Wei, Lijuan (Frontiers in Immunology, 2023)
Immune reconstitution inflammatory syndrome (IRIS) is characterized by exaggerated and dysregulated inflammatory responses that occur as a result of reconstitution of adaptive or innate immunity. A wide range of microorganisms have been found to be associated with IRIS, such as human immunodeficiency virus (HIV), Mycobacterium and actinobacteria. Whipple disease (WD) is an infectious disorder caused by the Gram-positive bacterium Tropheryma whipplei (T. whipplei) and IRIS also serves as a complication during its treament. Although many of these pathological mechanisms are shared with related inflammatory disorders, IRIS in WD exhibits distinct features and is poorly described in the medical literature. Novel investigations of the intestinal mucosal immune system have provided new insights into the pathogenesis of IRIS, elucidating the interplay between systemic and local immune responses. These insights may be used to identify monitoring tools for disease prevention and to develop treatment strategies. Therefore, this review synthesizes these new concepts in WD IRIS to approach the feasibility of manipulating host immunity and immune reconstitution of inflammatory syndromes from a newer, more comprehensive perspective and study hypothetical options for the management of WD IRIS.